2015
DOI: 10.1002/lary.25557
|View full text |Cite
|
Sign up to set email alerts
|

Recreational motor vehicle use and facial trauma

Abstract: As there is a significant potential for injury, familiarity with injury patterns associated with RMVs is useful in the management of facial trauma. Recreational motorized vehicles facial trauma results in tens of thousands of ED visits annually. This data reinforces the importance of pursuing further efforts to raise public awareness and improve safety measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…It is no surprise that the most common facial fracture was of the nose (75.1%), as is seen in baseball and recreational motor vehicle use. 8,11 Most of the facial fractures were caused by direct headon-head collision between players. Faude et al 5 reported that 40% to 60% of all soccer injuries were due to direct collision with another player or solid object, and Gianotti et al 31 found that increasing age was associated with more injuries from direct player-to-player contact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is no surprise that the most common facial fracture was of the nose (75.1%), as is seen in baseball and recreational motor vehicle use. 8,11 Most of the facial fractures were caused by direct headon-head collision between players. Faude et al 5 reported that 40% to 60% of all soccer injuries were due to direct collision with another player or solid object, and Gianotti et al 31 found that increasing age was associated with more injuries from direct player-to-player contact.…”
Section: Discussionmentioning
confidence: 99%
“…This database has been of great importance in numerous prior analyses. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In November 2015, the most recent 5-year period of data was searched using the product code "soccer" with focus on injuries specific to the face. Data were recorded and evaluated for patient age, sex, injury type, area of face, and a brief narrative description of the incident.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the NEISS uses validated algorithms created by the CPSC, utilizing cluster variables and sample weighting to calculate estimates of national injury incidence totals for large‐scale data interpretation. Secondary to these strengths, the NEISS has been utilized in numerous analyses spanning a variety of medical specialties …”
Section: Methodsmentioning
confidence: 99%
“…Injuries are commonly sustained while riding recreational motorized vehicles, like all-terrain vehicles (ATVs), dune buggies, go-carts, minibikes, dirt bikes, mopeds, tricycles, golf carts or utility vehicles, [1][2][3] due to the lack of standard safety features (airbags, seatbelts, enclosed walls) typically found in cars. Like cars, it is illegal to operate these recreational vehicles while intoxicated.…”
Section: Introductionmentioning
confidence: 99%